A new pH sensor localized in the Golgi apparatus of Saccharomyces cerevisiae reveals unexpected roles of Vph1p and Stv1p isoforms - Deschamps, Antoine; Colinet, Anne-Sophie; Zimmermannova, Olga; Sychrova, Hana; Morsomme, Pierre (Scientific reports, 2020)
The gradual acidification of the secretory pathway is conserved and extremely important for eukaryotic cells, but until now there was no pH sensor available to monitor the pH of the early Golgi apparatus in Saccharomyces cerevisiae. Therefore, we developed a pHluorin-based sensor for in vivo measurements in the lumen of the Golgi. By using this new tool we show that the cis- and medial-Golgi pH is equal to 6.6-6.7 in wild type cells during exponential phase. As expected, V-ATPase inactivation results in a near neutral Golgi pH. We also uncover that surprisingly Vph1p isoform of the V-ATPase is prevalent to Stv1p for Golgi acidification. Additionally, we observe that during changes of the cytosolic pH, the Golgi pH is kept relatively stable, mainly thanks to the V-ATPase. Eventually, this new probe will allow to better understand the mechanisms involved in the acidification and the pH control within the secretory pathway.
Keywords: Chemical Engineering; chemické inženýrství; Vacuolar Proton-Translocating ATPases; Saccharomyces cerevisiae; koncentrace vodíkových iontů; vakuolární protonové ATPasy; Isoenzymes; Saccharomyces cerevisiae Proteins; Hydrogen-Ion Concentration; Saccharomyces cerevisiae - proteiny; Golgi Apparatus; izoenzymy; Biosensing Techniques; biosenzitivní techniky; Golgiho aparát